Experiência nos videogames: construções entre o game design e o jogador - Albiero, Diogo Rodrigues (2015)
This dissertation seeks to understand the relationship between game design and the player on the construction of experiences manufactured in videogames. Due to its interactive nature, we can understand that videogames are made by two instances in the construction of its language and experience: on one hand, the game design defines how the game will be; and on another, the player, key-element, interacts and renews the choices made for the game. The question of how the experiences in videogames happen is instigated through this mutuality. With this purpose we seek to understand the concept of experience through the duality proposed by Eduard Gámez, using Martin Heidegger s phenomenological perspective and John Dewey s pragmatic view. We then go to a practical approach on how to create the language of videogames, based on Jesse Schell, Tracy Fullerton, Jesper Juul and Jane McGonigal. After identifying the key-elements to understand how videogames configure their language, we switch to the player s perspective. By using Gámez s Core Elements of Gaming Experience, we seek to identify similar aspects from players experience and how they eventually conform a subjective outcome from playing. These theoretical pillars end up in the analysis of the game Heavy Rain. It allows the concepts and examples used in the text to be effectively analyzed as a whole. The bibliographical revision and the approach given during the dissertation allow the evaluation of videogames under the game design and the player s perspective, heading towards the creation of the experience of this media on a mutual path. Through this we can see videogames from a wider point of view, understanding its processes and the potential they carry in their core as a media